2015
DOI: 10.1111/jdv.13237
|View full text |Cite
|
Sign up to set email alerts
|

Analytical evaluation of nine serological assays for diagnosis of syphilis

Abstract: In resourced settings, where the reverse sequence algorithm is preferred for screening, an automated treponemal immunoassay for initial screening subsequently followed by the TrepSure test or TP-PA assay as a second treponemal assay appear highly effective. Finally, a quantitative highly sensitive non-treponemal assay, e.g. the Macro-Vue RPR Card test, could then be used as a supplementary test to evaluate activity of the syphilis infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…The Syphilis Ultrarapid Test Strip (ABON, Alere) has 20-minute turnaround time. It is a chromatographic treponemal antibody immunoassay and the sensitivity of similar treponemal tests has been documented at 96–100% compared to a gold standard of TPPA [17]. Nontreponemal testing was not performed to help distinguish active from prior syphilis infection.…”
Section: Methodsmentioning
confidence: 99%
“…The Syphilis Ultrarapid Test Strip (ABON, Alere) has 20-minute turnaround time. It is a chromatographic treponemal antibody immunoassay and the sensitivity of similar treponemal tests has been documented at 96–100% compared to a gold standard of TPPA [17]. Nontreponemal testing was not performed to help distinguish active from prior syphilis infection.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the classical reverse algorithm and two European Union algorithms evaluating EIA (enzyme immunoassay) or CLIA (chemiluminescence assay) could predict confirmatory TPPA results [14], but the TTPA titer was not tested. The reverse sequence screening algorithms on nine serological assays for diagnosis of syphilis also indicate an initial treponemal immunoassay screening subsequently followed by a second TrepSure test or TP-PA assay [15]. These algorithms suggested that multi-assay-based diagnosis of syphilis is labor-intensive and costless.…”
Section: Discussionmentioning
confidence: 99%
“…Treponemal evaluation tests, used in reverse algorithm, are automated immunoassays and the microplate enzyme immunoassays are suitable for first screening, whilst the TPPA particle agglutination is more adaptive to be used as a second, confirmatory treponemal assay (23).…”
Section: Traditional Diagnostic Algorithmmentioning
confidence: 99%